Molecular pathways underlying sympathetic autonomic overshooting leading to fear and traumatic memories: looking for alternative therapeutic options for post-traumatic stress disorder - Azevedo, Márcia; Martinho, Raquel; Oliveira, Ana; Correia-de-Sá, Paulo; Moreira-Rodrigues, Mónica (Frontiers in Molecular Neuroscience, 2024)
The sympathoadrenal medullary system and the hypothalamic-pituitary-adrenal axis are both activated upon stressful events. The release of catecholamines, such as dopamine, norepinephrine (NE), and epinephrine (EPI), from sympathetic autonomic nerves participate in the adaptive responses to acute stress. Most theories suggest that activation of peripheral β-adrenoceptors (β-ARs) mediates catecholamines-induced memory enhancement. These include direct activation of β-ARs in the vagus nerve, as well as indirect responses to catecholamine-induced glucose changes in the brain. Excessive sympathetic activity is deeply associated with memories experienced during strong emotional stressful conditions, with catecholamines playing relevant roles in fear and traumatic memories consolidation. Recent findings suggest that EPI is implicated in fear and traumatic contextual memories associated with post-traumatic stress disorder (PTSD) by increasing hippocampal gene transcription (e.g., Nr4a) downstream to cAMP response-element protein activation (CREB). Herein, we reviewed the literature focusing on the molecular mechanisms underlying the pathophysiology of memories associated with fear and traumatic experiences to pave new avenues for the treatment of stress and anxiety conditions, such as PTSD.